Pengaruh Return On Asset (ROA) dan Earning Per Share (EPS) Terhadap Harga Saham Pada PT. Mitra Keluarga Karyasehat, Tbk. - Rostini, Rostini; Ismail, Muhammad; Bakri, Risna Melati Sukma; Goeliling, Ardhi; Iriani, Nisma (Jayapangus Press, 2024)
This research aims to investigate the influence of Return On Asset (ROA) and Earning Per Share (EPS) on stock prices at PT. Mitra Keluarga Karyasehat Tbk, a healthcare service company listed on the Indonesia Stock Exchange. Data for the study were obtained from the company's financial reports retrieved from the official website of the Indonesia Stock Exchange. The research method employed was literature review, analyzing relevant literature to understand the company profile and fundamental concepts related to ROA, EPS, and stock prices. Quantitative data from financial reports were used for empirical analysis. The findings indicate a significant relationship between ROA, EPS, and the stock price of PT. Mitra Keluarga Karyasehat Tbk. These findings provide valuable insights for investors and company management in developing effective investment strategies. This research contributes significantly to understanding the factors influencing stock prices of companies in the Indonesian equity market, as well as their implications for investment decisions and company management.